The integration paradigm of geography - Gladkey, Alexander; Golubchikov, Iurii (Human Geography Journal, 2016)
The processes of natural and humanitarian integration in the geography are described. The humanistic geography (or human geography, anthropogeography), is seen as an integrating methodology for geography which combines the principles of natural sciences and humanities. The general scientific problems connected with the dehumanization of knowledge as well as with differentiation of sciences are rethinking. The history of geographical paradigms development is explored. Anthropogeographical paradigm (anthropogeography), which combines the principles of natural sciences and humanities, prevailed in Russian geography of the early XX century and then turned out to be uncalled by Marxist-Leninist philosophy. Positivist paradigm, connected with dehumanization of knowledge as well as with differentiation of sciences, held dominating position in Soviet geographical school. The role of postmodern worldview in the development of post-disciplinary knowledge is revealed. The introduction subject in the scientific knowledge is defined.The role of geography in development of humanistic scientific values and post-disciplinary knowledge is based. The development of the humanism in geographic sciences is analyzed in the historical aspect. The current problems of “mechanistic approach” in geography are investigated. The necessity of perfection of current system paradigm with entering of humanistic elements is substantiated. It is offered four ways for paradigm transformation: 1) from anthropocentrism to humaneness; 2) from systematicity to humanistic synergy; 3) from quantitative methods to its further qualitative analysis and humanistic interpretation; 4) from territorial differentiation to philosophic fundamentals of global geo-space.